164 Beyond early intervention – integrated working in a brain tumour clinic. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Campbell, Carolyn; Peck, Josephine; Teague, Victoria; Minear, Fiona; Baldry, Glad; Gibbins, Jane; Stevens, Deborah
Abstract : Background: An increasing body of evidence supports early palliative care involvement in oncology as improving quality of life, advance care planning and decision making. Patients with brain tumours experience high symptom, social and psychological burden and those with lower grade tumours may struggle to access palliative care services earlier in their disease trajectory. This tumour site has not been studied in any previous work on early intervention or joint working. This service review looks at a joint oncology/palliative care, consultant delivered, brain tumour clinic. Methods: Records of 133 consecutive consultations (82 patients) were analysed for demographics, diagnosis, clinician seen, primary purpose of appointment and additional topics addressed. For a cohort of patients from each diagnostic group, all consultations since diagnosis were reviewed to establish any patterns of engagement over time and disease progression. Results: 43.6% of consultations were with the palliative care consultant (PCC). Longitudinally, 81.8% of patients saw the PCC at least once. Whilst PCC (60.3%) and oncologist (62.6%) had a similar proportion of complex consultations (those dealing with at least one additional topic) for the oncologist these were concentrated in new patient consultations and treatment decisions (63%) and for patients with glioblastomas (60.1%); whereas for the PCC, complex consultations were distributed across all tumour types except pituitary and predominantly occurred in routine reviews (76.5%). Levels of complexity were comparable in patients with lower grade gliomas or meningioma to those with glioblastomas. Conclusions: This analysis demonstrates a high level of complex need in patients with brain tumours and particularly for those with lower grade tumours over the very prolonged course of their disease. Integrated working appears to facilitate early involvement of palliative care and collaborative care, with patients accessing the most appropriate clinician for their current needs.